2011
DOI: 10.4314/pamj.v10i0.72239
|View full text |Cite
|
Sign up to set email alerts
|

Virological profile of pregnant HIV positive women with high levels of CD4 count in low income settings: Can viral load help as eligibility criteria for maternal triple ARV prophylaxis (WHO 2010 option B)?

Abstract: Introduction The objective of the study was to determine HIV-1 RNA load profile during pregnancy and assess the eligibility for the maternal triple antiretroviral prophylaxis. It was an observational cohort of pregnant HIV positive women ignorant of antiretroviral therapy with CD4 cell count of>350/mm 3 Methods Routine CD4 cell count assessment in HIV positive pregnant women completed by non exclusive measurement of the viral load by PCR /ARN in those wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…11 Our findings also revealed that the majority of the sero-positive participants were infected with HIV-1, a similar finding from other reports in Cameroon, which demonstrated that HIV-1 is the predominant type in the country. 15,16 The mean CD4 count of 546 (+179) cells/mm 3 was similar to those obtained from studies in Yaoundé, Cameroon, 17 and North-Rift, Kenya. 12 The relatively high mean CD4 count in the majority of the sero-positive participants may be indicative of recent HIV infection.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…11 Our findings also revealed that the majority of the sero-positive participants were infected with HIV-1, a similar finding from other reports in Cameroon, which demonstrated that HIV-1 is the predominant type in the country. 15,16 The mean CD4 count of 546 (+179) cells/mm 3 was similar to those obtained from studies in Yaoundé, Cameroon, 17 and North-Rift, Kenya. 12 The relatively high mean CD4 count in the majority of the sero-positive participants may be indicative of recent HIV infection.…”
Section: Discussionsupporting
confidence: 79%
“…9 The mean viral load (at log 10 4.4 copies/mL) was similar to that reported by Njom Nlend in 2011 in Yaoundé. 17 We found that 7 of 10 sero-positive pregnant women who were on ARVs before enrollment were experiencing virological failure. This finding poses a significant obstacle in the management of sero-positive pregnant women, especially as viral load testing still remains a scarce and expensive laboratory examination in this part of the world.…”
Section: Discussionmentioning
confidence: 79%